216k views
4 votes
Can you please help me with this. Last part of the question.

Can you please help me with this. Last part of the question.-example-1
Can you please help me with this. Last part of the question.-example-1
Can you please help me with this. Last part of the question.-example-2

1 Answer

0 votes

We know that function f(x) is given by


f(x)=x

where the slope is the coefficient of the variable x, that is, the slope,m, is


m=1

Since g(x) is given by


g(x)=6\cdot f(x)

we have that


g(x)=6x

where the slope is equal to 6, in other words


m\longrightarrow m=6*1=6

Therefore, the slope of the graph of g(x) is 6 times the slope of the graph of f(x).

Since the y-intercept of f(x) is zero, then the y-intercept of g(x) is zero too. Then, the answer is: the y-intercept does not change.

User Roderick Jonsson
by
4.9k points